Binge Eating Pattern Among School Students - V, RANJANA; GANAPATHY, DHANRAJ; SASANKA, KEERTHI (The journal of contemporary issues in business and government, 2020)
Binge eating disorder is when a person eats an excessive amount of food, losing control over what and how much is eaten, followed by feelings of guilt, shame or disgust. Factors like stress, food restriction, presence of palatable foods and environmental conditioning may also lead to binge in individuals. Early assessment and more extensive and suitable treatment may prevent more severe disorders. The main aim of this survey was to analyze binge-eating patterns among school students.Questionnaire was prepared and administered to 102 participants through a survey planet – an online survey. The study participants were people of age between 13-17. Data was collected from the link and was represented in the pie chart form. 31.2% binge eat more than 3 times a day, 32.3% binge eat more than 5 times a day, 19.4% binge eat more than 7 times a day. Stress, depression, negative feelings are some of the reasons, which influences binge eating, which is very common among school students. 48% consume more than normal level of calorie a day, 37.8% consume normal level of calorie, 13.3% consume less than normal level of calorie per day. Consumption of spicy food and junk food is also related to binge eating. Individuals with binge eating disorder experience impaired functioning in both social life and at home. From the survey, it was evident that binge eating is common among school students as the majority (32.3%) of them eat more than 5 times a day for which depression and hunger is the major cause.